Yield and Quality in Main and Ratoon Crops of Grain Sorghum Under Different Nitrogen Rates and Planting Densities - Zhou, Yu; Huang, Juan; Li, Zebi; Wu, Yu; Zhang, Jijun; Zhang, Yaqin (Frontiers in Plant Science, 2022)
Ratooning is the cultivation practice of two harvests in one cropping season by producing a second crop from the original stubble, which could provide higher resource use efficiency and economic benefit compared with direct sown crops. Nitrogen fertilizer (N) and planting density (D) play a vital role in sorghum (Sorghum bicolor L.) production; however, limited information is available on the effects on yield and quality of sorghum-ratoon system. To address this question, field experiments were conducted with three N treatments (120 kg N ha–1, N1; 180 kg N ha–1, N2; and 255 kg N ha–1, N3) and three D treatments (82 500 plant ha-1, D1; 105 000 plant ha-1, D2; and 127 500 plant ha-1, D3). The yield of main crop was significantly higher than that of ratoon crop. Increasing N could increase the yield and yield attributes of both main and ratoon crops, and the effect on the ratoon crop was greater than the main crop. With increasing D, grain yield of both main and ratoon crops increased, though 1000-grain weight and grain weight per ear decreased. The sorghum grain of ratoon crop contained higher starch, protein, and tannin contents, but lower fat content, indicating a better quality for liquor production. The quality traits were significantly affected by N and D, but the differences between treatments were smaller than that between main and ratoon crop. Our results indicated that increasing yield of ratoon crop could obtain high yield and quality of sorghum-ratoon system It was recommended that 120 kg N ha-1 with 127 500 plant ha-1 for main crop and a small N amount top dressed with three new buds left on stubble in each hill for ratoon crop.